Stress inside police departments: how the organization creates stress and performance problems in police officers - Shane, Jon M. (Routledge innovations in policing, 2020)
Police stress in today's world -- What methods should we use to research police stress -- Stress in policing: where does it come from? -- Stress in policing: what does it lead to? -- Stress in police work: what does the future hold?